I'd know you anywhere - Lippman, Laura, 1959- (New York W. Morrow, 2010)
Eliza Benedict's peaceful suburban life is shattered after she is contacted by Walter Bowman, the man who kidnapped and held her hostage as a teen in 1985, and who now claims to want forgiveness while on death row.
Keywords: Serial murderers -- Fiction; Death row inmates -- Fiction; Victims of crimes -- Fiction; Maryland -- Fiction; Psychological fiction; Suspense fiction